THE WORLD’S FIRST UNIVERSITY OF INDIGENOUS MATURITY: AN INNOVATIVE INITIATIVE IN THE AMAZON - Osório, Neila Barbosa; Neto, Luiz Sinésio Silva; Brito, Marlon Santos de Oliveira (Seven Editora, 2024)
Education is a fundamental right and an essential tool for personal, social and cultural development. In Brazil, educational programs seek to serve social groups, such as indigenous populations. In this context, the University of Maturity, of the Federal University of Tocantins, stands out with the creation of the first University of Indigenous Maturity in the world, aimed at the elderly of the indigenous population of the Amazon. The objective of this article is to present the creation and impacts of the University of Indigenous Maturity in Tocantínia, Tocantins, addressing its contribution to the social and educational inclusion of indigenous elders and the preservation of traditional knowledge through intergenerational educational programs. The research adopts a bibliographic approach, reviewing literature, consulting articles, government documents and university extension projects. Secondary data and reports about the University of Maturity and its extension aimed at indigenous populations were also analyzed. The results indicate that the University of Maturity has expanded its actions to include the indigenous population, becoming a pioneer in Brazil and in the world. The conclusions point out that the creation of the University of Indigenous Maturity in the Amazon represents a milestone in international education, promoting the social inclusion of a historically marginalized group. DOI:https://doi.org/10.56238/sevened2024.037-020